Data for the paper titled "Enhanced Asian warming increases Arctic amplification" - Yongkun Xie; Jianping Huang; Guoxiong Wu; Nan Lei; Yimin Liu (Zenodo, 2023)
This dataset isthe CESM outputs and codes and the observational datafor thestudy titled, " Enhanced Asian warming increases Arctic amplification ", which was submitted to Environmental Research Letters .There were four CESM experiments, namely HIST, AL500-sh0.5, amip-HIST, and amip-AL500-nosh. The observational data are the aridity index. This work was supported by the National Natural Science Foundation of China (91937302, 42030602) and Gansu Provincial Special Fund Project for Guiding Scientific and Technological Innovation and Development (2019ZX-06).